Leaders ought to know the 11 ground rules for common sense leadership - Van Hooser, Philip, 1957- (John Wiley & Sons, Inc., 2013)
From Phillip Van Hooser, leadership development advisor to hundreds of top U.S. companies, Leaders Ought to Know teaches all leaders - newly promoted, mid-level, or executives - eleven common sense, universal ground rules that "leaders ought to know" if they intend to lead with purpose, confidence, and effectiveness. By examining real-world examples of the dos and don'ts of leadership, executives and managers will gain practical strategies to transform the way they lead their employees. This comprehensive leadership development guide explains proven leadership concepts, including how to earn an employee's respect, the critical importance of truth-telling, a practical strategy for making impactful decisions, and ultimately how to be taken seriously as a leader. Learn how to do more of the right things, while avoiding the common leadership mistakes that trip up so many.